Writing ourselves into being: writing as spiritual self‐care for adolescent girls. Part One - Sinats, P. (International journal of children's spirituality, 2005)
This paper, the first of two parts, reports the claims of a participatory qualitative research project that explores the inner self‐awareness and self‐presentation of adolescent girls based on excerpts from their own adolescent writings. The participants selected material from their own diaries and poetry written between 1969–1999 (ages 11–17) that spoke to their adolescent spiritual concerns. The research team addressed questions of audience, voice, intention in writing and the role writing played in maintaining an inner life and sense of self. The persistent themes that arose were creating solitude, transforming to calm, preserving sensitivity, nurturing voice and connecting beyond the self, while the central identified theme was care of self. This first paper sets out context and process then addresses the first two themes. Part Two, to be published in a later edition of this journal, will explore the remaining themes and some implications for care work with adolescent girls.